2023
DOI: 10.1017/jfm.2023.252
|View full text |Cite
|
Sign up to set email alerts
|

Effects of gravity on natural oscillations of sessile drops

Abstract: Natural oscillations of sessile drops with a free or pinned contact line in different gravity environments are studied based on a linear inviscid irrotational theory. The inviscid Navier–Stokes equations and boundary conditions are reduced to a functional eigenvalue problem by the normal-mode decomposition. We develop a boundary element method model to numerically solve the eigenvalue problem for predicting the natural frequencies. Emphasis is placed on the frequency shifts of modes due to gravity for a wide r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 53 publications
1
7
0
Order By: Relevance
“…Conversely, as Bo increases, it is found that the lowest mode of a drop with α > 90 • gradually switches from mode {2, 0} to {1, 2}, with the consequence that for sufficiently high Bo the mode {1, 2} is the lowest mode regardless of the contact angle. As observed by Zhang et al (2023), this result implies that for large drops (and movable CL), non-axisymmetric oscillation will more likely manifest in large drops than in smaller ones.…”
Section: Overviewsupporting
confidence: 51%
See 4 more Smart Citations
“…Conversely, as Bo increases, it is found that the lowest mode of a drop with α > 90 • gradually switches from mode {2, 0} to {1, 2}, with the consequence that for sufficiently high Bo the mode {1, 2} is the lowest mode regardless of the contact angle. As observed by Zhang et al (2023), this result implies that for large drops (and movable CL), non-axisymmetric oscillation will more likely manifest in large drops than in smaller ones.…”
Section: Overviewsupporting
confidence: 51%
“…The system of governing equations, free-surface and CL conditions can be turned into an eigenvalue problem through the normal mode expansion ψ(x, t) = φ(r, z)e iλt e ilϕ and η(s, ϕ, t) = y(s)e iλt e ilϕ , where λ is the unknown complex eigenvalue. Zhang et al (2023) tackle such a problem through a BEM, which can deal with arbitrary drop geometry, with the advantage of reducing the two-dimensional problem to a boundary integral equation. The modes are then classified by the pair {n, l}, where the latter is the azimuthal wavenumber and the former indicates the number of vertical layers of the perturbation, which is related to the polar wavenumber of spherical harmonics introduced in (1.1) as n = (k − l)/2 + 1.…”
Section: Overviewmentioning
confidence: 99%
See 3 more Smart Citations